D’ iN Luggage / Muhammad Ridzauddin Ridzwan - Ridzwan, Muhammad Ridzauddin (2020)
Travel is an important aspect where travelers cannot simply ignore the role of luggage. Before beginning our travel, it is important to think about the right luggage necessary to keep all the needs of the traveler. Your Destination Enterprise is my company name develops "D'iN Luggage" which is a short version of "Duo in Luggage". This product comes with lots of specialties to make the luggage easier for travelers to use and different from any luggage because this product is designed with modern and advanced technology. Figure 1 below shows the logo of my company. Basically, this product is a friendly user product that helps people save time and energy. It will ease and minimize the time for people who are always busy. "D'iN Luggage" is a technological innovation product used by people to travel. It is a luggage that is built with multifunctional technology and safety devices. This product includes the most innovative and multifunctional technology system developments. It is very convenient to use for all users, especially travelers who will be on short trips or holidays.